Incarceration: punishment or rehabilitation? - McCoy, Erin L. (Today's debates, 2020)
The history of american prisons -- Challenges and controversy in us prisons -- Education and health care -- Violence behind bars -- Juveniles in the prison system -- Detaining immigrants -- Life in prison or parole? -- Choosing between rehabilitation and punishment -- Glossary -- Further information -- Bibliography -- Index -- About the authors.